Designing Malaysian identity: the taxi as an exemplar case study : an exploratory study of Malaysian identity and Malaysian product design templar - Amirul Fahmi Razali
In Malaysia, there are different understandings of the term 'design', where it appears to be perceived by many as being about the artistic beauty and function of the object created, rather than the process leading to it. This is evident through the review of literature, and major companies' R&D activities, where the demand in the Malaysian market is about the finished products, rather than the whole design process and the values behind the creation. The issue arises when there is no significant effort by the designers towards embedding the society's values or cultural elements into their design products. Then comes the question of what is the role of designers here? Can Malaysian designers succeed in designing Malaysian character products that portray the identity of the nation? Dismissed as disposable, cultural uniqueness and its values haven't been explicitly addressed in most Malaysian design approaches, let alone in the academic writing, which represents a severe omission of past research and current design scenarios in Malaysia. The objectives of this study were: investigating the relationship of design to culture; reviewing current efforts by Malaysians to produce Malaysian identity products; concluding the value and significance of culture as product identity; and making recommendations of a suitable design process in developing Malaysian identity design. These have been achieved through interviews with stakeholders; conducting case studies to strengthen the knowledge of local culture; and making recommendations as to how future designers can succeed in designing Malaysian identity recommendations as to how future designers can succeed in designing Malaysian identity products through focus group studies. A more precise view of the importance of Malaysia having a strong identity in their designed products by incorporating the cultural values of the societies has been established through these processes. To reflect these issues, this study has selected taxi design as the case study to justify the importance of identity in design, based on arguments in the literature. It has become self-evident that there is a need for more collaborative and coherent efforts from various parties to ensure that Malaysian designers will succeed in developing Malaysian identity products in the future.